2021
DOI: 10.1002/mrd.23458
|View full text |Cite
|
Sign up to set email alerts
|

The growth hormone and insulin‐like growth factor 1 axis in cattle during the peri‐ovulatory period activates the synthesis and release of oviductal contraction related substances

Abstract: Growth hormone (GH) and insulin‐like growth factor 1 (IGF1) are crucial for female reproductive functions. The cyclic regulation of the local GH/IGF1 axis in the oviduct and its involvement in oviductal contraction in cattle has not been investigated. Thus, the messenger RNA (mRNA) expression for GH receptor (GHR), IGF1, IGF1 receptor (IGF1R) in the whole oviducts, as well as in cultured bovine oviductal epithelial cells (BOECs) were evaluated. The GHR, IGF1, and IGF1R mRNA expression was significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Therefore, research on the establishment of an in vitro cell and tissue culture-based model mimicking the 3-dimensional (3D) structure of FTs awaits advancement of co-culture techniques and equipment for functional study as well as further discoveries are needs of the hour. The use of a microfluidic chamber could be further explored for the establishment of a 3D FT model for a TEP study [10] , where whole oviduct organ culture with microdialysis has revealed more details in other animals like bovines [11] . However, available little data confirm the existence of menstrual cycle-dependent human tubal luminal secretions [12] .…”
Section: Human Fallopian Tubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research on the establishment of an in vitro cell and tissue culture-based model mimicking the 3-dimensional (3D) structure of FTs awaits advancement of co-culture techniques and equipment for functional study as well as further discoveries are needs of the hour. The use of a microfluidic chamber could be further explored for the establishment of a 3D FT model for a TEP study [10] , where whole oviduct organ culture with microdialysis has revealed more details in other animals like bovines [11] . However, available little data confirm the existence of menstrual cycle-dependent human tubal luminal secretions [12] .…”
Section: Human Fallopian Tubesmentioning
confidence: 99%
“…PGs act through G-protein coupled receptors (GPCR), including four subtypes of PGE receptor (EP) (EP 1 , EP 2 , EP 3 , EP 4 ), PGF receptor (FP), PGI 2 receptor (IP), and PGD 2 receptor (DP) isoforms DP 1 and DP 2 [50,51] . Additionally, PGI 2 may act through a nuclear peroxisome proliferator-activated receptor-δ (PPAR-δ) [11] . Empirical evidence exists for the role of PGs in the human FT [52][53][54][55][56][57] .…”
Section: Prostaglandins and Early Embryo-ft Interactionsmentioning
confidence: 99%
“…IGF1 has a speci c growth hormone-binding receptor protein (IGFBP) and a growth hormone-binding receptor protein with speci c play IGF receptor, a supernatural endocrine growth hormone and an endocrine and paracrine growth regulator of its own [28,29]. The role of IGF1 in growth has been relatively well studied, with the main focus on livestock [30], and relatively little research and reporting in aquaculture. Davis et al and others studied polymorphisms in the IGF1 gene and found that this gene polymorphism had a signi cant effect on weight gain and milk yield growth in cows [31].…”
Section: High-resolution Genetic Mapmentioning
confidence: 99%